The Value of Common Laboratory Markers in Predicting the Severity of COVID-19 Patients - Chen L; Jiang YH; Li MY; Huang B; Yuan L; Wan JH; Qin TY; Zeng TT; Chen QG (Infection and Drug Resistance)
Lian Chen,1,* Yu-Huan Jiang,2,* Mei-Yong Li,3 Bo Huang,3 Lei Yuan,2 Jin-Hua Wan,2 Ting-Yu Qin,2 Ting-Ting Zeng,2 Qing-Gen Chen2 1Department of Ultrasound Medicine, The First Affiliated Hospital of Nanchang University, Nanchang, Jiangxi, People’s Republic of China; 2Department of Clinical Laboratory, The First Affiliated Hospital of Nanchang University, Nanchang, Jiangxi, People’s Republic of China; 3Department of Clinical Laboratory, The Second Affiliated Hospital of Nanchang University, Nanchang, Jiangxi, People’s Republic of China*These authors contributed equally to this studyCorrespondence: Qing-Gen Chen, Department of Clinical Laboratory, the First Affiliated Hospital of Nanchang University, Nanchang, 330006, People’s Republic of China, Tel/Fax +86 0791-86319420, Email 272880243@qq.comPurpose: The aim of the present study was to identify more effective laboratory markers to assess the severity of corona virus disease 2019 and predict the progression of the disease by collecting more laboratory markers and variables.Patients and Methods: In this study, most risk factors, including epidemiological characteristics, blood cell counts, cytokines, and infection markers, were collected from 126 patients with COVID-19 to assess their predictive value.Results: The area under curve (AUC) of Albumin (Alb) to fibrinogen (Fib) ratio (AFR) (0.791), Lactate dehydrogenase (LDH) (0.792), myoglobin (MYO) (0.795), C-reactive protein (CRP) (0.801) and lymphocyte count (0.859) were higher than other markers to distinguish severe from non-severe patients in receiver operating characteristic (ROC) analysis. In the univariate logistic regression analysis, thirty-six out of 46 risk factors, including 34 laboratory markers, were significantly associated with increased odds of severe patients. Multivariate logistic regression analysis showed that the CD19+ lymphocyte count, MYO, LDH, and AFR were associated with increased odds of severe disease. Moreover, Lymphocyte count and AFR levels increased, LDH and CRP levels decreased during hospitalization in recovered severe patients, whereas severe lymphocytopenia and continuously increasing LDH levels were observed in deteriorated patients. AFR level increased and CRP level decreased before the disease worsened in the deteriorated patients; however, when the patients deteriorated, AFR decreased and CRP increased significantly.Conclusion: CD19+ lymphocyte count, MYO, LDH, and AFR are independent biomarkers for early identification of severe COVID-19. Lymphocyte count, AFR, LDH, and CRP levels were helpful in predicting the clinical progression of the disease.\. Keywords: Albumin to fibrinogen ratio, C-reactive protein, Lymphocyte, Coronavirus Disease 2019, Inflammation